Local Climatological Data Summary: White Hall, Illinois, 1901-1990 - Bryan, Audrey A.; Armstrong, Wayne (Illinois State Water Survey, 1991)
White Hall (Greene County) has a temperate continental climate, dominated by maritime tropical air from the Gulf of Mexico from about March through October. Gulf air generally supports relative humidities of about 60% during the day and 85% at night. During these months, there are occasional, brief interruptions of drier, cooler air from the Pacific Ocean, but typically only last for a few days. From November through March, the White Hall area is dominated by Pacific Ocean air. Four to six times each winter, cold, dry air from the Canadian Arctic breaks south, bringing temperatures into the teens and occasionally below zero. Average annual precipitation is about 36 inches, varying from about 21 inches in 1930 and 1953, to 51 inches in 1970. The greatest monthly precipitation was 15.77 inches in September 1926 and the least a trace in January 1986. is peer reviewed Submitted by Agnes Stankiewicz (stankie2@illinois.edu) on 2014-10-29T15:12:37Z No. of bitstreams: 1 ISWSMP-98-5.pdf: 270718 bytes, checksum: eedc888bcd348344981df30257847ae3 (MD5) Made available in DSpace on 2014-10-29T15:12:38Z (GMT). No. of bitstreams: 1 ISWSMP-98-5.pdf: 270718 bytes, checksum: eedc888bcd348344981df30257847ae3 (MD5) Previous issue date: 1991 published or submitted for publication Open